Three new species of Rhipidocladum (Poaceae: Bambusoideae: Arthrostylidiinae) from South America - Tyrrell, Christopher D.; Clark, Lynn G. (Phytotaxa, 2013)
Three new woody bamboo species from South America, Rhipidocladum arenicolum from Peru, R. cordatum from Ecuador and R. rubrofimbriatum from Venezuela, are here described and illustrated. Based on morphological analysis, R. arenicolum and R. cordatum are placed in sect. Rhipidocladum and R. rubrofimbriatum in sect. Racemiflorum. Rhipidocladum arenicolum and R. cordatum are most similar to R. harmonicum, but R. arenicolum differs in its wider foliage leaf blades and longer spikelets and florets. Rhipidocladum cordatum differs by having cordate culm leaf blades, more branchlets per node and smaller, narrower foliage leaf blades as well as more closely spaced spikelets. Rhipidocladum rubrofimbriatum is most similar to R. sibilans but is awnless, has fewer branchlets per node, and larger, wider foliage leaf blades.